PODER EMPREGATÍCIO PELA ORDEM CONSTITUCIONAL (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
This article aims to research the employment power and its dimensions, namely the directive, regulatory, supervisory and disciplinary power, thus demonstrating how workers managed to improve their relations in the business world by the Constitution that guarantees their rights in many aspects. Keywords: Employment power. Dimensions of employment powers. Constitution. Labor Law.